Evaluation of Total Antioxidant Activity and Oxidative Stress in Seminal Plasma from Dogs Supplemented with Fish Oil and Vitamin E - Risso, Analía Lorena (2021)
Background: We evaluated the effect of fish oil (FO) and FO in addition to vitamin E (VE) supplementation on total antioxidant activity of dog seminal plasma, and further assessed oxidative stress. Additionally, we measured the effect of this supplementation on hematological parameters and serum biochemistry. Materials and Methods: In this experimental study, six male dogs were assigned to one of the following three groups for a period of 60 days using a replicated 3×3 Latin square design: control (CG), FO (FOG) and FO in addition to VE (FOEG). On days 0 and 60 of the trial, semen and blood samples were obtained. 2,2V-azino-bis (3-ethylbenzothiazoline- 6-sulfonate) (ABTS) and ferric reducing antioxidant power (FRAP) assays were used to determine total antioxidant activity. Oxidative stress was determined by measuring total sulfhydryl group (T-SH). Results: Dogs supplemented with FO alone had a lower total antioxidant activity in seminal plasma (ABTS: -59.86% vs.CG and -57.3% vs. FOEG; and FRAP: -37.3% vs. CG and -40.5% vs. FOEG), and higher oxidative stress (T-SH: +53.0% vs. CG and+60.2% vs. FOEG) compared with the other two groups (P<0.05). Serum triglyceride (TG) concentration decreased in FOG and FOEG compared with CG, on day 60 (P<0.01). Conclusion: We concluded that total antioxidant activitydecreased and oxidative stress increased in seminal plasma of dogs after FO supplementation for 60 days.